Rethinking Older Adult Murder Victims: Looking Back at 25 Years of Homicide Studies to Inform Future Research Needs - Addington, Lynn A. (Homicide studies, 2022)
Over the past 25 years, homicide researchers have largely ignored older adults. This pattern continues even in light of the ongoing demographic shift associated with the aging baby boomer generation. This article reflects on the current state of the literature and discusses areas in need of attention. Future research needs can be categorized into substantive and methodological issues. The insights gained by exploring these topics can generate nuanced explanations for fatal violence against older adults and support future evidence-based prevention policies.